An Efficient Genetic Transformation and CRISPR/Cas9-Based Genome Editing System for Moso Bamboo (Phyllostachys edulis) - Huang, Biyun; Zhuo, Renying; Fan, Huijin; Wang, Yujun; Xu, Jing; Jin, Kangming; Qiao, Guirong (Frontiers in Plant Science, 2022)
Moso bamboo (Phyllostachys edulis) is the most important monopodial bamboo species worldwide. The lack of genetic transformation system makes it difficult to verify the function of genes controlling important traits and hampers the process of molecular breeding in moso bamboo. Here, we established the plant regeneration system from immature embryos. Calli were induced on the MS medium added 2,4-D 4~6 mg·L-1 with high efficiency more than 60%. The PGR combination of NAA 0.5 mg·L-1, BAP 2.0 mg·L-1 and ZT 3.0 mg·L-1 were suitable for shoot differentiation, and the shoot induction frequency was increased to 43% after 0.5 mg·L-1 ABA pre - treatment. The effective antibiotic screening concentration was determined by hygromycin sensitivity test. We further optimized the Agrobacterium concentration and added vacuum infiltration for infection, which improved the transient expression efficiency. The genetic transformation system was established for the first time in moso bamboo and the transformation efficiency was approximately 5%. In order to optimize the genome editing efficiency, two endogenous U3 snRNA promoter was isolated from moso bamboo and used for driving sgRNA expression. The results showed that PeU3.1 promoter performed higher efficiency and used for in following genome editing in moso bamboo. Finally, homozygous pds1pds2 mutants were obtained by an efficient CRISPR/Cas9 genome editing system. These technical systems will be conducive to gene functional validation and accelerate the breeding process of moso bamboo.